Atlas of interventional neurology (Demos Medical, 2009)
Cerebrovascular disease is an important cause of morbidity and mortality worldwide but endovascular procedures are rapidly expanding the spectrum of treatment for CV disease. Atlas of Interventional Neurology is the first comprehensive review of the basic principles of endovascular treatment of cerebrovascular disease. It takes readers logically through each step of the procedures, reflecting real-time decision-making scenarios while highlighting anatomic landmarks and details. Concise instructions are presented in bulleted form, and indications and alternative methods are discussed where appropriate.